Immunological monitoring of extracorporeal photopheresis after heart transplantation. (April 2014) - Dieterlen, M.‐T.; Bittner, H. B.; Pierzchalski, A.; Dhein, S.; Mohr, F. W.; Barten, M. J.
Summary Extracorporeal photopheresis (ECP) has been used as a prophylactic and therapeutic option to avoid and treat rejection after heart transplantation (HTx). Tolerance‐inducing effects of ECP such as up‐regulation of regulatory T cells (Tregs) are known, but specific effects of ECP on regulatory T cell (Treg) subsets and dendritic cells (DCs) are lacking. We analysed different subsets of Tregs and DCs as well as the immune balance status during ECP treatment after HTx. Blood samples were collected from HTx patients treated with ECP for prophylaxis (n = 9) or from patients with histologically proven acute cellular rejection (ACR) of grade ≥ 1B (n = 9), as well as from control HTx patients without ECP (HTxC; n = 7). Subsets of Tregs and DCs as well as different cytokine levels were analysed. Almost 80% of the HTx patients showed an effect to ECP treatment with an increase of Tregs and plasmacytoid DCs (pDCs). The percentage of pDCs before ECP treatment was significantly higher in patients with no ECP effect (26·3% ± 5·6%) compared to patients who showed an effect to ECP (9·8% ± 10·2%; P = 0·011). Analysis of functional subsets of CD4+CD25highCD127low Tregs showed that CD62L‐, CD120b‐ and CD147‐positive Tregs did not differ between the groups. CD39‐positive Tregs increased during ECP treatment compared to HTxC. ECP‐treated patients showed higher levels for T helper type 1 (Th1), Th2 and Th17 cytokines. Cytokine levels were higher in HTx patients with rejection before ECP treatment compared to patients with prophylactic ECP treatment. We recommend a monitoring strategy that includes the quantification and analysis of Tregs, pDCs and the immune balance status before and up to 12 months after starting ECP.